Profile of tivozanib and its potential for the treatment of advanced renal cell carcinoma - Cowey CL (Dove Medical Press, 2013)
C Lance CoweyBaylor-Sammons Cancer Center, Texas Oncology, PA, US Oncology Research, Dallas, TX, USAAbstract: Tivozanib is a novel vascular endothelial growth factor receptor tyrosine kinase inhibitor (VEGF TKI). Among other VEGF TKIs, tivozanib stands apart due to its selective kinase inhibitory properties as well as its high potency for inhibiting VEGF receptors 1 and 2. Tivozanib has been evaluated in several clinical trials including a Phase I and Phase II trial demonstrating safety and efficacy for patients with advanced clear cell renal cell carcinoma (RCC). A pivotal randomized Phase III trial comparing the front-line use of tivozanib to sorafenib in patients with metastatic clear cell RCC has been reported. The clinical development of tivozanib and results of these important studies will be reviewed. Also, the potential placement of tivozanib among currently US Food and Drug Administration approved agents for advanced RCC will be discussed.Keywords: tivozanib, AV-951, metastatic renal cell carcinoma, RCC, VEGF inhibitor, targeted therapy, angiogenesis inhibitor